Efficacy and safety of repeated dosing of netupitant, a neurokinin‐1 receptor antagonist, in treating overactive bladder. Issue 3 (14th June 2013) - Haab, F.; Braticevici, B.; Krivoborodov, G.; Palmas, M.; Zufferli Russo, M.; Pietra, C.
Abstract Aim NK‐1 receptors in sensory nerves, the spinal cord and bladder smooth muscle participate in complex sensory mechanisms that regulate bladder activity. This study was designed to assess the efficacy and safety of a new NK‐1 receptor antagonist, netupitant, in patients with OAB. Methods This was a phase II, multicenter, double‐blind study in which adults with OAB symptoms >6 months were randomized to receive 1 of 3 doses of netupitant (50, 100, 200 mg) or placebo once daily for 8 weeks. The primary efficacy endpoint was percentage change from baseline in average number of daily micturitions at week 8. Urinary incontinence, urge urinary incontinence (UUI), and urgency episodes were also assessed. Results The primary efficacy endpoint was similar in the treatment groups (−13.85 for placebo to −16.17 in the netupitant 200 mg group) with no statistically significant differences between netupitant and placebo. The same was true for most secondary endpoints although a significant difference for improvement in UUI episodes and a trend for the greatest decrease in urgency episodes were seen in the netupitant 100 mg group. Netupitant was well tolerated with most treatment emergent adverse events (AEs) being mild. While the overall incidence of AEs increased with netupitant dose, there was no evidence for this dose dependency based on relationship to treatment, intensity, or time to onset. Conclusions The study failed to demonstrate superiority of netupitant versus placebo in decreasing OAB symptoms, despite a trend favoring netupitant 100 mg. There were no safety concerns with daily administration of netupitant over 8 weeks. Neurourol. Urodynam. 33:335–340, 2014. © 2013 Wiley Periodicals, Inc.